Detection and Molecular Characterization of Novel dsRNA Viruses Related to the Totiviridae Family in Umbelopsis ramanniana - Kartali, Tünde; Nyilasi, Ildikó; Szabó, Boglárka; Kocsubé, Sándor; Patai, Roland; Polgár, Tamás F.; Nagy, Gábor; Vágvölgyi, Csaba; Papp, Tamás (Frontiers in Cellular and Infection Microbiology, 2019)
Umbelopsis ramanniana is an oleaginous fungus belonging to the Mucoromycotina subphylum. Our group had previously detected four double-stranded RNA (dsRNA) bands in the U. ramanniana NRRL 1296 strain by gel electrophoresis. Here we describe the molecular characterization of its dsRNA elements as well as the discovery of four novel dsRNA viruses: Umbelopsis ramanniana virus 1 (UrV1), Umbelopsis ramanniana virus 2 (UrV2), Umbelopsis ramanniana virus 3 (UrV3), and Umbelopsis ramanniana virus 4 (UrV4). Full genomes of UrV1, UrV3, and UrV4 were determined using the full-length amplification of cDNAs (FLAC) technique; they contain two open reading frames (ORF), which putatively encode the coat protein (CP) and the RNA dependent RNA polymerase (RdRp), respectively. In case of UrV2, a partial ORF encoding a partial RdRp gene could be determined. Based on the phylogeny inferred from the RdRp sequences, UrV1 and UrV4 belong to the genus Totivirus, while UrV2 may belong to the genus Victorivirus. UrV3 nested to a novel, unclassified group of Totiviridae, which is related to the genus Totivirus. Hybridization analysis revealed that the dsRNA molecules of UrV1 and UrV4 correspond to the same 5.0-kbp electrophoretic band, whilst the probe for the UrV3 hybridized to the largest, 5.3-kbp and the 3.0-kbp bands of the dsRNA pattern of U. ramanniana. Interestingly, the probe for the UrV2 sequence did not hybridized to any dsRNA bands, but it could be amplified from the isolated 3.0-kbp fragment. By transmission electron microscopy, two different isometric virus particles with about 50 and 35 nm in diameter were detected in U. ramanniana NRRL 1296 indicating that this strain harbor multiple viruses. Beside U. ramanniana, dsRNA elements were also detected in other Umbelopsis isolates with different patterns consisting of 2 to 4 discrete and different sized (0.7–5.3-kbp) dsRNA molecules. Based on a hybridization analysis with UrV1 CP and RdRp probes, the bands with the size of around 5.0-kbp, which were present in all tested Umbelopsis strains, are presumed as possible full mycovirus genomes.